Uporaba tangrama pri pouku matematike na razredni stopnji - Lipovec, Alenka; Štukl, Maja (Revija za elementarno izobraževanje, 2010)
The tangram in lower primary mathematics. The tangram puzzle is a shape composing activity that is appropriate for the O-level of the Van Hiele geometrical thinking development theory. The focus of this article is the applicability of the seven-piece tangram with photography background in a school setting. The empirical data, collected using a semi-structured interview on a sample of 10 teachers, shows that teachers' knowledge concerning the effectiveness of the tangram is weak. The materials were evaluated through pedagogical experimentation and included 31 students in two classes (2nd and 5th). The contextualized environment was reinforced via photography as the underlying context of the tangram puzzle. The materials enhanced motivation even in the higher grades of lower primary education and positively influenced the students' solving capabilities.